PENERAPAN MODEL PEMBELAJARAN PARTISIPATIF AKTIF , KREATIF , EFEKTIF , DAN MENYENANGKAN (PAKEM) UNTUK MENINGKATKAN HASIL BELAJAR IPA SISWA KELAS IV SD NEGERI 51 PEDEKIK - Muhairi Muhairi; Zariul Antosa; Lazim.N Lazim.N (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract : This research is motivated by the low learning outcomes IPA fourth grade students of SD Negeri 51 Pedekik, with an average grade 57.67. While the value of a minimum completeness criteria (KKM) IPA is 65. Among the students who totaled 15 people only 14 people who reach KKM. This study is a Classroom Action Research (CAR) conducted aims to improve learning outcomes IPA fourth grade students of SD Negeri 51 Pedekik by applying participatory learning model, active, creative, effective, and fun (PAKEM). Data collection instruments in this thesis is the teacher and student activity sheets and learning outcomes. This thesis presents the results of studying the data obtained from the average results of study before action 57.67 rise 86.66% to 66.00 in cycle I. In the second cycle increased to 93.33% with an average of 80.00. The activities of teachers in the first cycle of the first meeting to obtain a percentage of 60.71% with the good category, at the second meeting has increased with the percentage of 71.42% both categories. Furthermore, the first meeting of the second cycle of teacher activity also increased with the percentage of 78.57% is very good category and at the second meeting of the second cycle increased again with a percentage of 89.28% is very good category. Activity of students in the first cycle of the first meeting to obtain the percentage of 60.71% less category, at the second meeting has increased with the percentage of 67.85% good category, in this cycle the students begin to understand the learning activities by applying participatory learning model, active, creative, effective and fun (PAKEM) is characterized by the activity of students in the second cycle the first meeting increased the percentage of 78.57% is very good category. At the second meeting of the second cycle increased with the percentage of 85.71% is very good category. Research results in the fourth grade Elementary School 51 Pedekik prove that the application of learning models of participatory, active, creative, effective and fun (PAKEM) can improve learning outcomes IPA fourth grade students of SD Negeri 51 Pedekik.Keywords : Participatory, active, creative, effective and fun (PAKEM), IPA Learning Outcomes